Stainless steel felt as diffusion backing for high-performance microbial fuel cell cathodes. Issue 57 (25th June 2015) - Qiu, Zhaozheng; Wei, Liling; Wang, Gang; Su, Min; Shen, Jianquan
<x xml:space="preserve">Abstract</x> Novel 3D air-cathodes were constructed using stainless steel felt as the diffusion backing and current collector for performance improvement of MFC.